2013
DOI: 10.1210/jc.2012-4253
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Healthy but Obese, a Matter of Time? Findings From the Prospective Pizarra Study

Abstract: The results suggest that MHO is a dynamic concept that should be taken into account over time. As a clinical entity, it may be questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
181
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(205 citation statements)
references
References 34 publications
17
181
2
5
Order By: Relevance
“…Some authors consider the appearance of metabolic abnormalities and other comorbidities associated with obesity to be only a matter of time; i.e., it is merely a question of evolution of the disease as evidenced by studies showing that MHO subjects exhibit increased risk of developing diabetes, hypertension, or metabolic syndrome in the long term (41,42). In this sense, a growing number of studies have questioned the apparently healthy metabolic condition of MHO, showing that these obese patients have increased morbidity and mortality as compared whiskers showing from minimum to maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider the appearance of metabolic abnormalities and other comorbidities associated with obesity to be only a matter of time; i.e., it is merely a question of evolution of the disease as evidenced by studies showing that MHO subjects exhibit increased risk of developing diabetes, hypertension, or metabolic syndrome in the long term (41,42). In this sense, a growing number of studies have questioned the apparently healthy metabolic condition of MHO, showing that these obese patients have increased morbidity and mortality as compared whiskers showing from minimum to maximum.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding that MH OWOB individuals were at no greater risk of CVD mortality than MH NW individuals suggests that such further discrimination may add little to CVD risk evaluation, consistent with CVD risk associated with increasing adiposity being fully explained by established risk factors (28). However, although increased sub-clinical inflammation in MHO may be relatively benign with regard to CVD risk, the increased insulin resistance may indicate increased risk of type 2 diabetes (26,29,30).…”
Section: Discussionmentioning
confidence: 73%
“…Also, in accord with our findings, the proportion of individuals MHO at baseline becoming MUH at follow-up was substantial at 30%. Likewise, Soriguer et al, in a study of 1051 individuals, found that 48% of those MH OB at baseline were MUH at a 6-year follow-up (30). However, in neither of these studies was the time profile of attrition of MH distinguished, there being only a single follow-up estimate of change in MH status.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy obese phenotype is characterized by preserved insulin sensitivity, relatively low visceral fat mass and normal adipose tissue function. However, initially MHO individuals undergo adverse metabolic changes associated with obesity over time, therefore metabolically healthy obesity may not be a stable condition [11,17,18]. While there were significant lower levels of low-density lipoprotein and triglycerides in MHO among patients younger than 40 years, the significance was lost among older patients.…”
mentioning
confidence: 99%